"Sadly and with a Bitter Heart": What the Caesarean Section Meant in the Middle Ages - Bednarski, Steven; Courtemanche, Andrée (Florilegium, 2011)
This article contextualizes the history of the so-called Caesarean section to argue that the history of obstetrics is written at the intersection of manifold cultural phenomena. The article presents a unique historical document, a notarized act of 1473 drawn up for a Provençal barber surgeon commissioned to extract a fetus from a corpse. The procedure it prescribes was technically a postmortem dissection, or sectio in mortua, a process linked to surgery and theology as much as to law, superstition, and inheritance. In addition to its analysis, the article presents a comprehensive critical historiography, a transcription and edition of its primary source, a table of other extant primary sources that reference sectiones in mortua, and a detailed bibliography.